Breakthrough SARS-CoV-2 infections after vaccination: a critical review - Zeinab Mohseni Afshar; Mohammad Barary; Rezvan Hosseinzadeh; Amirmasoud Alijanpour; Dariush Hosseinzadeh; Soheil Ebrahimpour; Kosar Nazary; Terence T. Sio; Mark J. M. Sullman; Kristin Carson-Chahhoud; Arefeh Babazadeh (Taylor & Francis Group, 2022)
At the beginning of the current pandemic, it was believed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection would induce lifelong immunity and that reinfections would be unlikely. However, after several cases of reinfection were documented in previously infected patients, this was understood to be a false assumption, and this waning humoral immunity has raised significant concerns. Accordingly, long-term and durable vaccine-induced antibody protection against infection have also become a challenge, as several breakthroughs of COVID-19 infection have been identified in individuals who were fully vaccinated. This review discusses the current evidence on breakthrough COVID-19 infections occurring after vaccination.